KAJIAN KUALITAS PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (STUDI PADA MALL PELAYANAN PUBLIK KABUPATEN SIDOARJO - Fani, Amrul; Eprilianto, Deby Febriyan (Publika, 2024)
The government is responsible for providing public services as an effort to fulfill the needs of thecommunity in the context of state life. Through various institutions that have been formed according totheir functions, the government tries to improve the welfare of the people for which it is responsible. Factsprove that public services in Indonesia still have several shortcomings and ignore their responsibilities inserving the community. Therefore, in this research, researchers are interested in examining public servicesin Sidoarjo Regency as a Public Service Mal which is famous for services that continue to innovate. Thisresearch uses a descriptive qualitative research method. Researchers collected data through a process ofobservation, interviews and documentation. This research found that the results of public services carriedout by employees at the Sidoarjo Regency Public Service Mal in the transparency indicator were that theapplicable SOPs were not clear, namely that the SOPs were only available on the website so that olderpeople were confused about looking for SOPs for making resident documents, accountability indicatorswere in accordance with services that prioritize the community and follow the rules of the Ministry of HomeAffairs, participatory indicators are good because providing good services makes people participate inmaking citizenship documents, conditional indicators still have shortcomings because the service stillprioritizes people in the disability group rather than regular people, indicators of equal rights are still thereare shortcomings because the service often carries out queue breaking so that the queue does not match theserial number obtained, the indicator of suitability of rights and obligations is good because there is acomplaint and question and answer service so that the public can easily get information in makingpopulation documents